(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study extensively studied the impact of proper nutrition during pregnancy on maternal and fetal health. The physiological and psychological importance of a balanced diet during pregnancy, as well as the possible negative consequences of malnutrition, were analyzed. The study developed joint recommendations based on the recommendations of Ibn Sina and the views of Western medicine.